2016
DOI: 10.1128/jb.00187-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ribosomal Protein Operons rplM-rpsI , rpmB-rpmG , and rplU-rpmA at the Transcriptional and Translational Levels

Abstract: It is widely assumed that in the best-characterized model bacterium Escherichia coli, transcription units encoding ribosomal proteins (r-proteins) and regulation of their expression have been already well defined. However, transcription start sites for several E. coli r-protein operons have been established only very recently, so that information concerning the regulation of these operons at the transcriptional or posttranscriptional level is still missing. This paper describes for the first time the in vivo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…6C). We hypothesized that this structure constituted a novel RARE and, indeed, a contemporaneous study found that L13 translationally represses the rplM - rpsI operon in vivo (Aseev et al, 2016). No RNA structure or mechanistic information has been reported for the putative L13-binding motif.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6C). We hypothesized that this structure constituted a novel RARE and, indeed, a contemporaneous study found that L13 translationally represses the rplM - rpsI operon in vivo (Aseev et al, 2016). No RNA structure or mechanistic information has been reported for the putative L13-binding motif.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, L13 binds RNA containing the H1–H5 RNA, and likely inhibits rplM translation by stabilizing H4 and occluding access to the RBS. L13 has also been shown to negatively regulate translation of the downstream rpsI gene (Aseev et al, 2016). Our structure models revealed that rpsI is structurally linked to rplM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the potential for incorrect ligand hypotheses, we list additional genes associated with the various motifs (Table 1 and Additional file 2). An additional point is that it is possible that some RNAs that regulate r-proteins in cis do not function by binding any r-protein [33].…”
Section: Analysis Of Ligands and Binding Sitesmentioning
confidence: 99%
“…Persisters are phenotypic variants that are formed through epigenetic changes that involve multiple redundant pathways to survive lethal antibiotic stress. These include toxin-antitoxin (TA) modules, stringent response (ppGpp) 14, 15 , DNA repair, metabolism 16 , energy production, protein degradation pathway (trans-translation), signaling pathways, antioxidant system, and efflux and transporters 17 18 . To better understand persister cells development and functioning, classical genetic processes is not sufficient, the epigenetic controlling gene expression is urgently required.…”
Section: Introductionmentioning
confidence: 99%